Deposição de A/N por sputtering não reativo - Damasceno, Eduardo Moreira (2011)
In this work we deposit via non-reactive magnetron sputtering of radio-frequency nanofilmes of nitreto of aluminum(AlN). The nanofilms aluminum nitride are semiconductors materials with high thermal conductivity, high melting point, piezoelectricity and wide band gap (6, 2 eV) with hexagonal wurtzite crystal structure, belonging to the group of new materials called III-V nitrides in which together with the gallium nitride and indium nitride have attracted much interest because they have physical and chemical properties relevant to new technological applications, mainly in microelectronic and optoelectronic devices. Three groups were deposited with thicknesses nanofilms time dependent on two substrates (glass and silicon) at a temperature of 25 ° C. The nanofilms AlN were characterized using three techniques, X-ray diffraction, Raman spectroscopy and atomic force microscopy (AFM), examined the morphology of these. Through the analysis of X-rays get the thickness of each sample with its corresponding deposition rate. The analysis of X-rays also revealed that nanofilms are not crystalline, showing the amorphous character of the samples. The results obtained by the technique, atomic force microscopy (AFM) agree with those obtained using the technique of X-rays. Characterization by Raman spectroscopy revealed the existence of active modes characteristic of AlN in the samples